2021
DOI: 10.2147/cia.s311773
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Minefield: Managing Refusal of Medical Care in Older Adults with Chronic Symptoms of Mental Illness

Abstract: The purpose of this case series is to illustrate the complexity of considerations across health (physical and mental), ethical, human rights and practical domains when an older adult with chronic symptoms of mental illness refuses treatment for a serious medical comorbidity. A broad understanding of these considerations may assist health care professionals in navigating this challenging but common aspect of clinical practice. Case Presentation: Three detailed case reports are described. Participants were older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 76 publications
(110 reference statements)
1
5
0
Order By: Relevance
“…These led them to treat older adult patients differently and consider caring for them pointless and time-consuming. Our findings were in line with other studies that reported misperceptions by healthcare team about old age and the inherent nature of certain symptoms with old age, 26 treating an older adult patient is pointless, 27 and they are not worthy of care. 28 In another study, Heydari and colleagues stated that there are misconceptions about older people and that they are perceived incapable of adapting to new situations, ineducable, impatient, irritable, and bad-tempered.…”
Section: Discussionsupporting
confidence: 92%
“…These led them to treat older adult patients differently and consider caring for them pointless and time-consuming. Our findings were in line with other studies that reported misperceptions by healthcare team about old age and the inherent nature of certain symptoms with old age, 26 treating an older adult patient is pointless, 27 and they are not worthy of care. 28 In another study, Heydari and colleagues stated that there are misconceptions about older people and that they are perceived incapable of adapting to new situations, ineducable, impatient, irritable, and bad-tempered.…”
Section: Discussionsupporting
confidence: 92%
“…While the evaluation of clinician knowledge about capacity assessment and related legal frameworks is beyond the scope of the current study, they are relevant practical aspects of health care decision-making, which may also be affected by mentalist attitudes. 11 Addressing doctors' stigma regarding PLWMI is a core clinical implication of this study. According to Knaak and Patten, 32 targeting the roots of stigma in health care through evidence-based initiatives is a fundamental starting point.…”
Section: Discussionmentioning
confidence: 95%
“…10 Mentalism is a major barrier to quality treatment and care. 9,11 Stigmatisation of people with mental illness acts as a barrier to physical health care across all areas of the health care system 7,9 and the poorer health outcomes of PLWMI continue throughout the lifespan, including at the end of life. 5,12 These negative end-of-life outcomes for PLWMI include poorer symptom management, such as pain management, 13 less engagement in advance care planning 14 and significantly lower likelihood of accessing specialist care, including palliative care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will focus on one paper as an example. When we searched the database using the above keywords, we found four categories of papers: (1) written mainly from the perspective of ethicists or philosophers [ 1 , 2 , 3 ]; (2) written mainly from a clinical perspective [ 4 , 5 , 6 , 7 , 8 ]; (3) written mainly from the perspectives of other fields such as law [ 9 , 10 , 11 ]; (4) written mainly by interdisciplinary expert authors such as clinicians and ethicists [ 12 , 13 , 14 , 15 , 16 ]. All categories have merits and demerits.…”
Section: Introductionmentioning
confidence: 99%